Analysis of Environmental Accounting Application of Waste Management Operational Costs at RSU Gmim Kalooran Amurang - Moses C. Liando; Victorina Z. Tirayoh; Lady D. Latjandu (PT FORMOSA CENDEKIA GLOBAL, 2023)
Environmental crises or problems are an important focus that must be considered immediately considering the poor management of this waste has a real impact on the environment. Living things in this case humans play a role in pollution of the environment, but the main characters in pollution are manufacturing companies and perhaps many more profit and non-profit organizations that are directly involved in environmental pollution. The purpose of this study was to find out what the application of environmental accounting was in waste management at RSU GMIM Kalooran Amurang. This research is a descriptive qualitative research type. Descriptive research is research that is directed to provide symptoms, facts or events systematically and accurately, regarding the characteristics of a particular population or area. The results showed that RSU GMIM Kalooran Amurang in carrying out the waste management process was good but RSU GMIM Kalooran Amurang had not implemented environmental accounting properly because they had not disclosed the elements of costs in detail about waste management in their cost reports.